EXTERNAL FAILURE COSTS AND THEIR ROLE IN BANKING SERVICE PRICING-AN APPLIED STUDY AT AL-RAFIDAIN BANK - Hadeel Hisham Adham (Scholars Digest Publishing, 2025)
Recent technological developments in the business environment and increased competition have prompted banks to adopt modern methods that contribute to improving the quality of banking services by providing the best banking services with a high level of quality that achieves customer satisfaction. The problem addressed in this study is the lack of an effective system for measuring costs in banking organizations, despite the the importance of quality-related costs, but the measurement and determination of these costs is not accurate, and an appropriate price for banking services has not been determined. The study aims to show the impact of the external failure costs of banking services on their pricing. The study produced a set of conclusions and recommendations. Iraqi banks were selected as the study population, specifically Rafidain Bank (General Administration) as the study sample. The research sets out to achieve its objectives based on a basic hypothesis, which is that external failure costs affect the pricing of banking services. The study relied on an analysis of the financial statements of Rafidain Bank, the study sample, and the period analyzed was 2021-2017. One of the most important conclusions reached by the study is that measuring quality costs is essential for any bank interested in improving the quality of its services and supporting its survival and continuity in the market. Disclosing this information in separate reports helps provide detailed information on its main elements (prevention costs, evaluation costs, external failure costs, and internal failure costs) and gives the bank's management a clear picture of the role of each element in improving quality and its impact on service pricing. The most important recommendations that emerged from the study are that banks should focus on determining quality costs, classifying them according to their categories, measuring them, and disclosing them, given their role in improving the quality of banking services provided to customers and the impact of these costs on the pricing of banking services.
Keywords: Quality costs, external failure costs, pricing of banking services.